2006
DOI: 10.1080/14764170600607731
|View full text |Cite
|
Sign up to set email alerts
|

Red light‐emitting diode (LED) therapy accelerates wound healing post‐blepharoplasty and periocular laser ablative resurfacing

Abstract: In this small series of 10 patients, red LED phototherapy after blepharoplasty and laser ablative resurfacing cut the time to resolution of side effects and the healing time by one-half to one-third compared with contralateral unirradiated controls. Further studies are warranted with larger populations to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 3 publications
1
47
0
1
Order By: Relevance
“…As more evidence of the statistically proven benefits of LLLT in animal trials have surfaced, some researchers have begun to shift their view to whether this treatment may have any beneficial properties in human wound healing. There have been more recent studies as of late examining and challenging the significance of LLLT in human subjects [8][9][10] . The overall conclusion from this review is that, although there have been some positive results stemming from studies looking at LLLT in animal and even some in humans, there is limited research supporting the approach in human subjects.…”
Section: Resultsmentioning
confidence: 98%
“…As more evidence of the statistically proven benefits of LLLT in animal trials have surfaced, some researchers have begun to shift their view to whether this treatment may have any beneficial properties in human wound healing. There have been more recent studies as of late examining and challenging the significance of LLLT in human subjects [8][9][10] . The overall conclusion from this review is that, although there have been some positive results stemming from studies looking at LLLT in animal and even some in humans, there is limited research supporting the approach in human subjects.…”
Section: Resultsmentioning
confidence: 98%
“…However, Trelles et al concluded that further studies were warranted with larger populations to confirm these findings [22]. Trelles et al, in a small series of ten patients, have used red LED phototherapy (20 minutes, 96 J/cm2, 633 nm), after blepharoplasty and laser ablative resurfacing.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The LED (light emitting diode) arises with the development of technological systems of light production and emission, being a hopeful alternative for tissue repair therapy (Meyer et al, 2010;Sousa et al, 2010;Trelles and Allones, 2006). Despite this fact, the number of researches about this technique comparing LILT to LED therapy is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…LED therapy and LILT have been used to irradiate surgical incisions in order to accelerate the postoperative recovery (Trelles and Allones, 2006). However, some specific surgeries require equally specific care.…”
Section: Introductionmentioning
confidence: 99%